Waves of Protest : Popular Struggle in El Salvador, 1925-2005 - Almeida, Paul, 1968- (Book collections on Project MUSE., 2008)
One of the first longitudinal studies of collective resistance in the developing world, Waves of Protest examines large-scale contentious action in El Salvador during critical eras in the countrys history. Providing a compelling analysis of the massive waves of protests from the early twentieth century to the present in El Salvador, Paul D. Almeida fully chronicles one of the largest and most successful campaigns against globalization and privatization in the Americas. Drawing on original protest data from newspapers and other archival sources, Almeida makes an impassioned argument that regim.